Consumer behaviour on the e-commerce market in the light of empirical research in Lubuskie voivodeship = Zachowania konsumenta na rynku e-commerce w świetle wyników badań empirycznych w województwie lubuskim - Kułyk, Piotr; Michałowska, Mariola (Zielona Góra: Faculty of Economics and Management Press)
The main aim of this article was to identify the behavior of consumers in the e-commerce market in Poland, according to the model of e-customer as adopted by Meier and Stormer. An attempt was made to answer the following questions: whether education has an impact on the propensity to make purchases over the Internet and the level of concern about Internet security, what are the greatest limitations of e-commerce, whether there is a clear link between the assessment of the overall impression of shopping online and satisfaction with service.
Keywords: zachowania konsumentów; model e-klienta; klient; Lubuskie; consumer behavior; model of e-customer; e-commerse; customer; lubuskie voivodeship